I sikh, 'calvinisti' in Val Padana (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. L’etica del lavoro - 3. I simboli identitari - 4. Il gurdwara come risorsa sociale - 5. Il kirpan - 6. Il valore di un riconoscimento.Sikhs, Calvinists in the Po ValleyABSTRACT: Sikhs are an important component of the New Religious Pluralism (NRP) that, especially due to the migratory flows of last decades, we record in Italy today. Many Sikh workers are employed in the dairy farming sector and, at least in the North of the country, they appear to be well integrated. This process has been facilitated by strict work ethics grounded in their theology. Nevertheless, to date the Sikh community has not been legally recognized as a religious body. Efforts by Sikh representatives to adopt a kirpan (ritual dagger) compatible with Italian law have not produced the desired results. However, there is still an urgent need for legal recognition of a faith community that has achieved important and successful integration processes in just a few decades.